Multi-criteria spatial decision analysis for demarcation of greenway: A case study of the city of Rio Claro, São Paulo, Brazil - Giordano, Lucilia do Carmo; Riedel, Paulina Setti [UNESP] (Elsevier B.V., 2008)
Concern regarding hydrological resources has been a theme of growing importance in Brazil, associating the development of new management policies and maintenance of natural areas related to rivers. An efficient way to maintain natural areas around rivers has been the development of greenways, and some cites have already adopted specific legislation in this respect. Following this growing evolution in the treatment of hydrological resources, this study was carried out to demarcate a greenway along the Corumbatai River in the state of São Paulo, Using multi-criteria analysis in a GIS environment. First, thematic maps were elaborated based on Landsat 7 satellite, aerial photographs and digital topographic base, Supported by field activities. With the use of multi-criteria analysis, for which ad hoe consultations were conducted to attribute weights to the thematic maps, a suitability map was elaborated for the allocation of the greenway. Sites that should be included in the greenway were also selected, such as areas appropriate for leisure activities, and ecologically important areas. Based on the suitability map, a pathway analysis was done, connecting the relevant points of interest, thus generating a greenway that runs along the Corumbatai River, with the aim of contributing to the conservation of this important hydrological resource. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: greenways; environmental planning; rivers; multi-criteria analysis; GIS